HUBUNGAN STRESS KERJA DENGAN PERILAKU MEDIKASI DI RUANG AL-QOMAR DAN ASY-SYAM RUMAH SAKIT ISLAM SURAKARTA - Sigit Iswanto; Okti Sri Purwanti (Universitas Muhammadiyah Surakarta, 2008)
Research background: room of Al-Qomar and Asy-Syam have the high stressor. Job system which is not well design, can cause the sigh subjektive, heavy work load, is not effective and inefficient which is on its innings can generate the work, so that downhill work productivity. Target of research is analysis the relation between stress work behaviorally medication of nurse in Al-Qomar and Asy-Syam Room of Islamic Hospital Surakarta. This research is including type of research of observational and explanatory because direct observation researcher and analysis the relation stress work behaviorally medication. This research use the instrument research in the form of questioner and checklist. This research take the sample 22 respondent by taking entire or all population. Analysis this research use the formula of correlation by using level signifikansi (α: 0,05).Result the research is: there are relation which significan between variable stress work the (work load, situation work, and relation interpersonal) behaviorally medication in Al-Qomar and Asy-Syam room in Islamic Hospital of Surakarta, with the value rcount = -0,856 and α : 0,000. so that excelsior stress work hence progressively lower the behavior medication. Referring to research result which have been conducted by hence researcher have the suggestion to related or relevant institution to be able manage the stress nurse so that expected can improve the performance, behavioral and quality of job. Need the existence of furthermore research to know the other factors causing behavioral degradation medication